PENGARUH LINGKUNGAN TERHADAP HASIL BELAJAR SISWA PELAJARAN IPS KELAS VIII SEMESTER GENAP DI SMP NEGRI 3 PANJI KABUPATEN SITUBONDO - Firman Jaya (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The results of student learning is the assessment of learning activities that have been performed and the shape of the final formulation is given by the teacher to see the extent to which the student's ability that is expressed in simbu, numbers, letters and sentences to reflect the results already achieved. Environment is to include all of the conditions in this world in certain ways affect behavior, growth, perkambangan or lifeprocesses kecualai genes and even genes can also be seen as preparing the environment (to provide envirnment) for other genes. The learning environment is an important determinant of student success in order to achieve the desired learning outcomes. Researchers the object of eighth grade students study as many as 100 people.Afterdata analysis and testing hypotheses, can be assessed the level of the correlation coefficient between the learning outcomes (Y) to the environment (X1) by ignoring the school environment (X2) and the community (X3) of 0.3044. While the value of the correlation coefficient between the level of learning outcomes (Y) with the school environment (X2) by ignoring the family lingkingan (X1) and the community (X3) of 0.2788, while the value of the coefficient level korekasi between learning outcomes (Y) with the community ( X3) with mengbaikan family environment (X1) and the school environment (X2) is 0.4228. And the value of the correlation coefficient between ketinga level bebes variables simultaneously with kriteriumnya Ry (1,2,3) as 0.604.Further proving the working hypothesis by using F major, major work will prove hypotension when the F-count is greater than F-table with singnifikan level of 5%. Large F-count was 18.373 while the F-table is 2.6994 at N = 100, mean F-count is greater than F-table dikatan segingga no significant influence of the environment on student learning outcomes VIII grade social studies in junior high school second semester Lesson 3